An Efficacy Study between High Viscosity Glass Ionomers and Resin Sealants in Fissure Caries Prevention: A 2-Year Split Mouth Randomized Controlled Trial - Haricharan, Praveen Bhoopathi; Voruganti, Sreenivas; Kotha, Arpitha; Mahalakshmamma Shivanna, Madhuniranjanswamy; Gandhi, Bhavana; Suresh, Nanditha (European Journal of Dentistry, 2021)
Objectives This clinical trial compared the efficacy of atraumatic restorative treatment (ART) sealants against resin-based sealants in terms of their retention and fissure caries preventive benefits over a period of 24 months among a section of school children in the Southern Indian state of Telangana.Materials and Methods A split mouth clinical trial employed 198 children, who received these sealants on their lower permanent first molars. Retention was assessed 6 monthly and caries annuallyStatistical Analysis Chi-square tests were utilized to analyze the retention rate and the incidence of dental caries between the two groups. Kaplan–Meier survival analysis plotted the cumulative survival percentage of partially, and fully retained sealants and the survival of dentin carious free pits and fissures among both the groups. A linear binary logistical regression analysis calculated the odds ratio.Results A statistical significant difference was observed in the retention rate between these sealants at every follow-up stage. The cumulative survival percentage of ART and resin sealants was calculated to be 30.9 and 37.5% by the end of 2 years. The Kaplan–Meier analysis showed no significant difference with regard to the survival of dentin carious free pits and fissures. The odds ratio for this trial was 0.747 (95% confidence interval: 0.493–1.13)Conclusion Resin sealants fared better than ART sealants in the field of retention. However, no significant differences were observed with regard to fissure caries prevention by the end of the study period.
Keywords: atraumatic restorative treatment; fissure sealants; glass ionomer sealants; resin-based sealants